Fostering reflective practice in Post Graduate Certificate in Education students through the use of reflective journals. Developing a typology for reflection. Issue 3 (4th May 2022) - Gadsby, Helen
ABSTRACT: This research argues a need for a shared understanding of reflective practice across all the stakeholders involved in initial teacher education and develops a typology for assessing reflective writing. During the course of the research, the experiences of eighteen Postgraduate Certificate in Education (PGCE) secondary students were explored. This was achieved through the use of questionnaires, semi- structured interviews and the analysis of reflective journals. This data collection was supported by post-course interviews of 4 students. A grounded theory informed approach was adopted. The results show that over the course of the year, all of the students improved in their ability to reflect, both in discussion with their mentors and in their written work. The typology that was developed as an outcome of the research is a useful tool to use with Initial Teacher Education (ITE) students when exploring what reflective practice is and how to write reflectively and as such has been used extensively within my own institution to support the development of reflective practice.